Vitamin A intakes remain higher among intervention participants 3 years after a biofortification intervention in Mozambique - de Brauw, Alan; Moursi, Mourad; Munhaua, Bernardino (Cambridge University Press, 2019)
The Reaching End Users (REU) project introduced orange sweet potatoes (OSP) to farmers in northern Mozambique between 2006 and 2009, and the associated cluster randomised control trial found increased vitamin A intake among targeted children and women of child-bearing age and reduced prevalence of inadequate vitamin A intake. Yet little is known about whether successful agricultural–nutrition interventions have lasting effects. This study measures the lasting effects of the REU project, 3 years after the project ended, on vitamin A intake. To do so, dietary intake data were collected in the same thirty-six villages as the original study, focusing on both women of child-bearing age and children under 6 years old, the latter including both children who had been measured before and younger children (under 3 years old) in the same farmer groups. The dietary intake is then converted to micronutrient intake to compare treated households with control households. Vitamin A intake remains higher in treated villages than in control villages among both children under 3 years old, who had not been born when the original intervention ended, and mothers of child-bearing age. Differences in vitamin A intake can wholly be attributed to differences in OSP intake. Therefore, the REU project appears to have had lasting impacts on vitamin A intake beyond the intervention period. Had the vine retention component been enhanced, lasting impacts could have been even larger.